Autologous stem cell transplantation for patients with early progression of follicular lymphoma: a follow-up study of 2 randomized trials from the German Low Grade Lymphoma Study Group - Jurinovic, Vindi; Metzner, Bernd; Pfreundschuh, Michael; Schmitz, Norbert; Wandt, Hannes; Keller, Ulrich; Dreger, Peter; Dreyling, Martin; Hiddemann, Wolfgang; Unterhalt, Michael; Hoster, Eva; Weigert, Oliver (Biology of blood and marrow transplantation, 2018)
Patients with follicular lymphoma (FL) and progression of disease (POD) within 24 months after frontline treatment (POD24) have poor overall survival (OS). The optimal salvage treatment for these patients is unknown. We assessed the role of high-dose therapy and autologous stem cell transplantation (ASCT) in transplant-eligible patients. We analyzed 162 patients with advanced-stage FL who had received frontline treatment within the GLSG1996 or GLSG2000 trials. All patients had POD at age ≤ 65 years and had not received a prior transplant. Second-line treatment was not specified by study protocols. Survival was calculated from time of second-line treatment. Eighteen patients (11%) progressed (n = 16) or died (n = 2) during cytoreductive second-line treatment (considered “cytoreduction failure”); none received ASCT, and their median second-line OS was <1 year. A total of 113 patients had POD24 (70%), whereas 49 had POD after 24 months (30%). Sixty-three patients without cytoreduction failure received ASCT (39%), and 81 received no transplant (50%). In patients with POD24, a significant survival benefit was associated with ASCT with a 5-year second-line progression-free survival for ASCT versus no transplant of 51% versus 19% (hazard ratio, .38; 95% confidence interval, .24 to .62; P < .0001) and a 5-year second-line OS of 77% versus 59% (hazard ratio, .54, 95% confidence interval, .30 to .95; P = .031). Thus, ASCT is an effective treatment option for transplant-eligible patients with high-risk FL as identified by POD24 and should be evaluated in prospective clinical trials.